Effect of extracts of Sargassum spp. in growth and antioxidants of tomato seedlings - Sariñana-Aldaco, Oscar; Benavides-Mendoza, Adalberto; Juárez-Maldonado, Antonio; Robledo-Olivo, Armando; Rodríguez-Jasso, Rosa María; Preciado-Rangel, Pablo; González-Morales, Susana (Ecosistemas y Recursos Agropecuarios, 2021)
Tomato is the most cultivated and consumed vegetable in the world and is frequently attacked by various environmental stresses that affect its bioproductivity. Possible solutions to mitigate stress include the use of biostimulants, in particular the use of brown algae extracts that positively affect various physiological and biochemical processes in plants. Therefore, the objective of thepresent work was to evaluate the effect of foliar application of 17 hydroalcoholic extracts of Sargassum spp. at 1.5% and two control treatments (distilled water and commercial product based on Ascophyllum nodosum) on the growth and antioxidant compounds of tomato seedlings, under a completely random design. The results show that the extract called EAS7 (160 °C/ 30 min/ 50% ethanol) presented the best results. EAS7 increased the height, stem diameter and total fresh and dry matter of tomato seedlings by 8.67, 32.32, 25.03 and 11.59%, respectively,compared to the absolute control  (distilled water). Also, EAS7 increased the content of proteins, glutathione, total phenols, flavonoids and antioxidant capacity (ABTS) of the leaves by 386.48, 15.92, 22.05, 35.99 and 18.86%, respectively, compared to the absolute control. The application of extracts of Sargassum spp. is a promising alternative to improve the agronomic and antioxidant characteristics of tomato crops.